Low-k nano-dielectrics facilitate electric-field induced phase transition in high-k ferroelectric polymers for sustainable electrocaloric refrigeration - Qiang Li; Luqi Wei; Ni Zhong; Xiaoming Shi; Donglin Han; Shanyu Zheng; Feihong Du; Junye Shi; Jiangping Chen; Houbing Huang; Chungang Duan; Xiaoshi Qian (Nature Communications, 2024)
Abstract Ferroelectric polymer-based electrocaloric effect may lead to sustainable heat pumps and refrigeration owing to the large electrocaloric-induced entropy changes, flexible, lightweight and zero-global warming potential. Herein, low-k nanodiamonds are served as extrinsic dielectric fillers to fabricate polymeric nanocomposites for electrocaloric refrigeration. As low-k nanofillers are naturally polar-inactive, hence they have been widely applied for consolidate electrical stability in dielectrics. Interestingly, we observe that the nanodiamonds markedly enhances the electrocaloric effect in relaxor ferroelectrics. Compared with their high-k counterparts that have been extensively studied in the field of electrocaloric nanocomposites, the nanodiamonds introduces the highest volumetric electrocaloric enhancement (~23%/vol%). The resulting polymeric nanocomposite exhibits concurrently improved electrocaloric effect (160%), thermal conductivity (175%) and electrical stability (125%), which allow a fluid-solid coupling-based electrocaloric refrigerator to exhibit an improved coefficient of performance from 0.8 to 5.3 (660%) while maintaining high cooling power (over 240 W) at a temperature span of 10 K.